The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1039/d2sc00864e
|View full text |Cite
|
Sign up to set email alerts
|

Energy transfer (EnT) photocatalysis enabled by gold-N-heterocyclic carbene (NHC) complexes

Abstract: We present the use of gold sensitizers [Au(SIPr)(Cbz)] (PhotAu 1) and [Au(IPr)(Cbz)] (PhotAu 2) as attractive alternatives to state-of-the-art iridium-based systems. These novel photocatalysts are deployed in [2+2] cycloadditions of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 44 publications
1
29
0
2
Order By: Relevance
“…For that, a deeper understanding of TTA[ 73 , 109 , 110 , 111 , 112 ] is required, and regarding sensitizer development, the upconversion community will strongly benefit from the recent progress in Dexter energy transfer catalysis. [ 49 , 113 , 114 , 115 , 116 ]…”
Section: Discussionmentioning
confidence: 99%
“…For that, a deeper understanding of TTA[ 73 , 109 , 110 , 111 , 112 ] is required, and regarding sensitizer development, the upconversion community will strongly benefit from the recent progress in Dexter energy transfer catalysis. [ 49 , 113 , 114 , 115 , 116 ]…”
Section: Discussionmentioning
confidence: 99%
“…5 c ,9 b , c These compounds have been successfully applied in organic synthesis 9 c and photocatalysis. 11 In addition, some of the CMA complexes have shown remarkable anticancer activity in several cell lines. 9 b , d To the best of our knowledge, all reported CMA complexes are mononuclear and dinuclear amido-bearing NHC complexes have not yet been described in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Having recently reported on the use of [Au(SIPr)(Cbz)]( PhotAucat 1 ) and [Au(IPr)(Cbz)] ( PhotAucat 2 ) as sensitizers in the [2 + 2] cycloaddition of diallyl ethers and N -tosylamides and having also shown that these gold–NHC complexes enabled the unprecedented photocatalytic intramolecular [2 + 2] cycloaddition of indoles, 5 c ,11 the structural similarities between these photocatalysts and the novel dinuclear [(bisNHC){Au(Cbz)} 2 ] complexes described here, we reasoned that two gold centers might also prove beneficial in EnT photocatalysis. 18,19 We next investigated the photocatalytic activity and photophysical properties of the new family of dinuclear bridging complexes to validate these suspicions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, coinage metal carbenes have found myriad applications in catalysis, OLEDs, and stimulus-responsive materials. 1,3,[5][6][7][8][9][10][11][12][13] Linearly coordinated systems featuring a donor-M-acceptor (D-M-A) structure often display thermally activated delayed fluorescence (TADF), bypassing the spin-forbidden phosphorescence from the T1 state by endothermic reverse intersystem-crossing (rISC) and subsequent S1"S0 emission. [7][8][9][14][15][16][17][18][19][20] With this alternative luminescence mechanism relevant for efficient triplet exciton harvesting in device technologies, radiative rate constants kTADF of 10 5 -10 6 s -1 can be achieved that are competitive or even higher than obtained with traditional 4d/5d metal complexes that provide spin-orbit coupling (SOC) for phosphorescence.…”
mentioning
confidence: 99%